Aplicação e modificação química da sílica gel obtida de areia - Prado, Alexandre G. S.; Faria, Elaine A.; Padilha, Pedro M. [UNESP] (Sociedade Brasileira de Química, 2005)
The silica gel was obtained from sand and its surface was modified with POCl3 to produce Si-Cl bonds on the silica surface. Ethylenediamine was covalently bonded onto the chlorinated silica surface. The adsorption of the chlorides of divalent cobalt, nickel and copper was qualitatively studied to show that the bonding of ethylenediamine onto the silica gel surface produces a solid base capable of chelating metal ions from solution. The experiments illustrate the extraction of silica gel, its reactivity, the development of modified surfaces and its application in removing metal ions from water and are deigned for undergraduate inorganic chemistry laboratories.
Aplication and chemical modification of silica-gel obtained from sand
Keywords: silica; teaching experiment; adsorption